2023
DOI: 10.1029/2023gl102826
|View full text |Cite
|
Sign up to set email alerts
|

Extensional Earthquakes in the Absence of Magma in Northern Afar: Insights From InSAR

Abstract: Recent observations from geology, geodesy and seismicity at magma-rich continental rifts suggest that dike intrusion is the primary mechanism achieving plate extension (Ebinger et al., 2010;Sigmundsson et al., 2015;Wright et al., 2012). In these settings most medium-to-large magnitude, normal slip earthquakes are induced by dikes, while purely tectonic normal faulting is less common (Ebinger et al., 2010). For example, in the magma-rich rifts of Ethiopia (Afar and the Main Ethiopian rift) all the geodetically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…North of Mount Dallol (Figure 1), a seismic swarm was recorded near Bada in December 2022, and interpreted as a consequence of plate spreading by pure tectonic extension (La Rosa et al, 2023). A seismic swarm had occurred at the same place in 1993 (Ogubazghi et al, 2004;La Rosa et al, 2023), and rupture propagation was found to be reminiscent of associated dike propagation (Ruch et al, 2021).…”
Section: Earlier Workmentioning
confidence: 99%
“…North of Mount Dallol (Figure 1), a seismic swarm was recorded near Bada in December 2022, and interpreted as a consequence of plate spreading by pure tectonic extension (La Rosa et al, 2023). A seismic swarm had occurred at the same place in 1993 (Ogubazghi et al, 2004;La Rosa et al, 2023), and rupture propagation was found to be reminiscent of associated dike propagation (Ruch et al, 2021).…”
Section: Earlier Workmentioning
confidence: 99%